Development of Nutraceutical Ready-to-Serve Blends of Ginger and Honey - Singh, J P; Mishra, Praveen K; Siddiqui, Mohammed Wasim; Ahmad, Md Shamsher; Aftab, M A; Kumar, Vinod (Journal of Postharvest Technology, 2014)
In the present investigation, an effort has been made to  prepare a therapeutic ready-to-serve (RTS) beverage using ginger  juice/extracts and honey. The blended RTS was prepared by  using different proportions of ginger juice and honeyT1- 5%  ginger extract + 10% honey, T2- 5% ginger extract + 15 % honey,  T3- 10% ginger extract + 10 % honey, T4- 10% ginger extract +  15 % honey and T5- 10% ginger extract without honey (Control),  which were stored under ambient conditions. The prepared RTS  were analyzed for different biochemical parameters as well as  sensory quality. Among the different blends, treatment (T2)  having 5% ginger extract + 15 % honey maintained the bio chemicals with the highest organoleptic quality throughout  storage period for overall acceptability.
Keywords: Ginger; Honey Ready-to-serve Beverage; Shelf life